Urban Transport in the Europe and Central Asia Region : World Bank Experience and Strategy - World Bank (Washington, DC, 2013)
The paper's main objectives are to provide a common thematic basis for urban transport inputs into the making of country-specific assistance strategies, and thereafter to guide urban transport project and sector work included in the business plans agreed under these strategies. It is a companion volume to the forthcoming ECA Transport Strategy Paper, which covers all modes of transport. It also represents a bridge between the project-related and policy studies done for specific cities/countries in ECA, and the Bank-wide urban transport policy, whose latest expression is the document Cities on the Move: The World Bank Urban Transport Strategy Review, published in August 2002. Also, urban transport activities being highly interdependent with other aspects of urban life and economy, this paper is related to parallel Bank writings on urban development, water, and environment in the ECA region.